El Currículo de Educación General Básica y su Adaptación para los Procesos de Inclusión Educativa de la Escuela Agustín Albán del Cantón Pujilí, provincia de Cotopaxi durante el Período Lectivo 2014-2015 - Rodríguez Morales, Juan Vicente (2016)
The main objective of the present investigation was adequate the Basic general education curriculum to achieve educative processes of inclusion into Agustin Albán School from Pujilí canton, Cotopaxi Province on academic year 2014 – 2015. This research represents the solution for the next investigative problem. How does curriculum of general education influence over educative inclusion processes on Agustin Albán School? The used methodology was; non experimental because no variables were managed; therefore natural phenomena was observed according its context. The conclusions were lack rights and duties practice on childhood, civil moments are not the integration space for students, neither sport and recreational practices do not contribute with the educative inclusion, sometimes conflicts are generated in the educative community. The contribution of this thesis is designing and systematization of educative inclusion strategies which ones let to generate equality conditions becoming the classroom into a place for integration and adequate for living.